Design, analysis and testing of a new piezoelectric tool actuator for elliptical vibration turning. (6th July 2017) - Lin, Jieqiong; Han, Jinguo; Lu, Mingming; Yu, Baojun; Gu, Yan
Abstract: A new piezoelectric tool actuator (PETA) for elliptical vibration turning has been developed based on a hybrid flexure hinge connection. Two double parallel four-bar linkage mechanisms and two right circular flexure hinges were chosen to guide the motion. The two input displacement directional stiffness were modeled according to the principle of virtual work modeling method and the kinematic analysis was conducted theoretically. Finite element analysis was used to carry out static and dynamic analyses. To evaluate the performance of the developed PETA, off-line experimental tests were carried out to investigate the step responses, motion strokes, resolutions, parasitic motions, and natural frequencies of the PETA along the two input directions. The relationship between input displacement and output displacement, as well as the tool tip's elliptical trajectory in different phase shifts was analyzed. By using the developed PETA mechanism, micro-dimple patterns were generated as the preliminary application to demonstrate the feasibility and efficiency of PETA for elliptical vibration turning.